“It's like a swan, all nice and serene on top, and paddling like hell underneath”: community first responders’ practices in attending patients and contributions to rapid emergency response in rural England, United Kingdom—a qualitative interview study - Gupteswar Patel; Viet-Hai Phung; Ian Trueman; Julie Pattinson; Vanessa Botan; Seyed Mehrshad Parvin Hosseini; Roderick Ørner; Zahid Asghar; Murray D. Smith; Elise Rowan; Robert Spaight; Jason Evans; et al. (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2023)
Abstract Background Community First Responder (CFR) schemes are a long-established service supplementing ambulance trusts in their local community in the United Kingdom. CFRs are community members who volunteer to respond to people with life-threatening conditions. Previous studies highlighted the motivations for becoming CFRs, their training, community (un)awareness and implications of their work on themselves and others. The practices of CFRs in prehospital care remain underexplored. Therefore, we aimed to explore real-world practice of Community First Responders and their contribution to prehospital emergency care. Methods We conducted 47 interviews with CFRs (21), CFR leads (15), ambulance clinicians (4), commissioners (2) and patients and relatives (5) from six ambulance services and regions of England, United Kingdom. Thematic analysis enabled identification of themes and subthemes, with subsequent interpretation built on the theory of practice wisdom. Results Our analysis revealed the embeddedness of the concept of doing the right thing at the right time in CFR practice. CFRs’ work consisted of a series of sequential and interconnected activities which included: identifying patients’ signs, symptoms and problems; information sharing with the ambulance control room on the patient’s condition; providing a rapid emergency response including assessment and care; and engaging with ambulance clinicians for patient transfer. The patient care sequence began with recognising patients’ signs and symptoms, and validation of patient information provided by the ambulance control room. The CFRs shared patient information with ambulance control who in turn notified the ambulance crew en-route. The practices of CFRs also included delivery of emergency care before ambulance clinicians arrived. Following the delivery of a rapid emergency response, CFRs engaged with the ambulance crew to facilitate patient transfer to the nearest medical facility. Conclusion The sequential CFR practices supported ambulance services in delivering prehospital and emergency care in rural areas. CFR practices were founded on the principle of practice wisdom where CFRs constructed their practice decisions based on the patient’s condition, their training, availability of equipment and medications and their scope of practice.